Some remarks on the logic of theology - Dadaczyński, Jerzy (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
The issue of the logic of theology so far have not been given so much attention neither from logicians nor from theologians. The first group seem not to consider the language of theology as a “place” to apply the results of their work. Also theologians are not particularly interested in that issue. The aim of this paper is to highlight one aspect of the issue of logic of theology, namely – the problem of the contradiction in the (language of) contemporary theology. In the first section, we show some of many examples of contradictions in contemporary theology. Next, the question regarding the reason of the existence so many examples of contradiction in theology is addressed. In the subsequent section, some problems generated by those contradictions are considered and a question if certain kind of logic would be able to deal with those problems is raised. Finally, some remarks regarding the need to take systematic research on logic (language) theology and the need to build analytic theology are postulated.